The influence of mild acidity on lysyl-phosphatidylglycerol biosynthesis and lipid membrane physico-chemical properties in methicillin-resistant Staphylococcus aureus. (August 2017) - Rehal, Reg P.; Marbach, Helene; Hubbard, Alasdair T.M.; Sacranie, Anam A.; Sebastiani, Federica; Fragneto, Giovanna; Harvey, Richard D.
Graphical abstract: Highlights: 31 P NMR is a sensitive, non-destructive method for lipid analysis in membranes containing aminoacyl phosphatidylglycerols. Membrane neutralisation in bilayers containing lysyl-phosphatidylglycerol is only achieved under mildly acidic conditions. Ion-pairing in lipid extracts containing fully-ionised L-PG elicits ordering effects in air/water interface monolayers. Increased quantities of fully-ionised L-PG in model membranes greatly reduce their interaction with antimicrobial peptides. Abstract: The increased biosynthesis of lysyl-phosphatidylglycerol in Staphylococcus aureus when cultured under conditions of mild acidity and the resultant increased proportion of this lipid in the plasma membrane of the bacterium, alters the physico-chemical properties of lipid bilayers in a manner which is itself dependent upon environmental pH. Clinically relevant strains of S. aureus, both methicillin susceptible and resistant, all exhibited increased lysyl-phosphatidylglycerol biosynthesis in response to mild environmental acidity, albeit to differing degrees, from ∼30% to ∼55% total phospholipid. Polar lipid extracts from these bacteria were analysed by 31 P NMR and reconstituted into vesicles and monolayers, which were characterised by zeta potential measurements and Langmuir isotherms respectively. A combination of increased lysyl-phosphatidylglycerol content and mild environmental acidity were found to synergistically neutralise the charge of the membranes, in one instance altering the zeta potential from −56 mV to +21 mV, and induce closer packing between the lipids. Challenge of reconstituted S. aureus lipid model membranes by the antimicrobial peptide magainin 2 F5W was examined using monolayer subphase injection and neutron diffraction, and revealed that ionisation of the headgroup α-amine of lysyl-phosphatidylglycerol at pH 5.5, which reduced the magnitude of the peptide-lipid interaction by 80%, was more important for resisting peptide partitioning than increased lipid content alone. The significance of these results is discussed in relation to how colonising mildly acidic environments such as human mucosa may be facilitated by increased lysyl-phosphatidylglycerol biosynthesis and the implications of this for further biophysical analysis of the role of this lipid in bacterial membranes.